Design And Development Of Power Conditioning Circuit For Impact-Based Piezoelectric Energy Harvester - Ahmad Nawir, Nur Amalina (2020)
Harvesting ambient energies from the surrounding can be realized by using piezoelectric mechanical transducer. This type of energy offering a prospect of powering low power electronic devices such as wireless sensor nodes which replacing the uses of batteries as the primary sources. Numerous studies have shown that the power densities of energy harvesting devices is around hundreds of microwatts. However, the power requirements for most electronic devices are in the range of micro to milliwatts. Furthermore, piezoelectric transducer generates high magnitude of output voltage; can reach up to hundreds Volts, but very low in term of current. This is the key challenge in developing an efficient power conditioning circuits that can offers an adequate output power for an optimum power transfer. In this project, a power conditioning circuits was developed for managing the power conversion process of a vibrational-based impact mode piezoelectric energy harvester. The proposed circuit should be able to enhance the generated output power from the piezoelectric by using a three conditioning units. It consists of an AC/DC rectifying circuits, step-down DC/DC buck converter and a storage capacitive bank. The power generator was implanted on the electrodynamic shaker with the acceleration level of 0.7 g at the resonant frequency of 42 Hz. Few power enhancement methods have been investigated in term of mechanical structural design and also on the proposed power conditioning circuitry itself. The generated output voltage from the harvester can be increased by 16.7% by using a proposed supporting base with a booster hole of 30 mm in diameter in order to increase the transducer’s strain displacement further. The analysis was conducted part by part before fully integrating them in a whole unit. For the first stage, the efficiency of the circuit can be enhanced by reducing the value of the parasitic components of the rectifying components; forward voltage drops of the diode, Vf and the capacitivity. The constructions of the rectifying circuits also affect the power conversion of the harvester system. It is found that full-wave Schottky bridge rectifier is the most efficient conversion circuit for piezoelectric energy harvester compared to the full-wave bridge MOSFET rectifier and specialized voltage doubler rectifier with 35.6% differences of 3.77 mW output power. Next, the system gets integrated with a regulated conversion circuit that has been designed to regulate at 3.3V with a hysteretic voltage mode control feedback system. As a conclusion, the proposed circuits managed to increase the regulated output current by 51.93% with the power conversion efficiency of 70.43% and 330 μW output power. A practical evaluation was conducted by employing an RF transmitter as the application load. It has been isolated first by using a push button during the capacitive charging process. It requires about 7.3 minutes to fully charge a 13.2 mF storage capacitor and able to transmit the encoded signal to the receiver in 16.03 s. For further improvement, the designs can be modified by employing the usage of supercapacitor as energy storage to increase the extracted output power of the harvester.